2010
DOI: 10.1590/s0101-20612010000400014
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização física e química da casca e polpa de jambo vermelho (Syzygium malaccensis, (L.) Merryl & Perry)

Abstract: O Jambo vermelho (Syzygium malaccensis, (L.) Merryl & Perry) pode ser consumido in natura, em forma de compotas, doce em massa, geleias, licores e aguardente e ainda pode ser utilizado para a produção de corante e antioxidante natural para uso em vários segmentos da indústria. Os frutos do jambeiro apresentam cor vermelho escuro, levemente adocicado, exalando aroma de rosas, persistente e bastante agradável ao olfato. As características físicas dos frutos, como cor, tamanho, número de sementes, quantidade de p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 7 publications
1
5
1
6
Order By: Relevance
“…For pulp percentage, there are reports in literature of very similar rates to that found in the present study (85.23%) Almeida (2011), 83.13%, Falcão et al (2002), 81.70% and Augusta et al (2010) 75.69%. For malay apple fruit length and width and seed width, the present work presented, respectively 5.79, 4.75 and 2.64 (cm), very close to what is reported in literature for this species, since Costa et al (2006) found 7.11, 5.15 and 2.33 cm respectively and Augusta et al (2010), 5.44 cm for length and 4.40 cm for fruit width.…”
Section: Botanic and Physiologysupporting
confidence: 89%
“…For pulp percentage, there are reports in literature of very similar rates to that found in the present study (85.23%) Almeida (2011), 83.13%, Falcão et al (2002), 81.70% and Augusta et al (2010) 75.69%. For malay apple fruit length and width and seed width, the present work presented, respectively 5.79, 4.75 and 2.64 (cm), very close to what is reported in literature for this species, since Costa et al (2006) found 7.11, 5.15 and 2.33 cm respectively and Augusta et al (2010), 5.44 cm for length and 4.40 cm for fruit width.…”
Section: Botanic and Physiologysupporting
confidence: 89%
“…A entrecasca apresentou quantidades significativas de cálcio (67,77mg 100g -1 ), ferro (0,51mg 100g -1 ) e fósforo (13,30mg 100g -1 ), comparados aos 0,036mg 100g -1 para cálcio, na casca de jambo (AUGUSTA et al, 2010) e 0,149mg 100g -1 de fósforo, e 6,4.10 -3 mg 100g -1 de ferro reportados para casca de C. xanthocarpa (VALLILO et al, 2008). Os dados justificam a utilização da entrecasca de melancia também como fonte de minerais importantes à saúde humana.…”
Section: Resultsunclassified
“…Some research has described the composition and properties of the fruits and stems of the plant; however its leaves have been poorly studied. Reports in recent scientific literature have shown that the leaves of S. malaccense are rich in phenolic compounds and flavonoids and present antioxidant and antiglycemic activities (Augusta, Resende, Borges, Maia, & Couto, 2010;Arumugam et al, 2014;Batista et al, 2017).…”
Section: Introductionmentioning
confidence: 99%